2020
DOI: 10.3390/su12187750
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Wind–PV Frequency Control Strategy under Variable Weather Conditions in Isolated Power Systems

Abstract: Over the last two decades, variable renewable energy technologies (i.e., variable-speed wind turbines (VSWTs) and photovoltaic (PV) power plants) have gradually replaced conventional generation units. However, these renewable generators are connected to the grid through power converters decoupled from the grid and do not provide any rotational inertia, subsequently decreasing the overall power system’s inertia. Moreover, the variable and stochastic nature of wind speed and solar irradiation may lead to large f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 71 publications
0
6
0
1
Order By: Relevance
“…Similar strategies were previously proposed in [65], where a cooperation between hydro‐power plants and FESSs was analysed. In addition, the authors suggested an alternative frequency strategy for PV power plants in [66], where the frequency controller included the VSWTs' rotational speed deviation as an input; and a coordination between hydro‐power and VSWTs in [67].…”
Section: Power‐frequency Controlmentioning
confidence: 99%
“…Similar strategies were previously proposed in [65], where a cooperation between hydro‐power plants and FESSs was analysed. In addition, the authors suggested an alternative frequency strategy for PV power plants in [66], where the frequency controller included the VSWTs' rotational speed deviation as an input; and a coordination between hydro‐power and VSWTs in [67].…”
Section: Power‐frequency Controlmentioning
confidence: 99%
“…To model a synchronous machine of a PMSG, projection of phase quantities in a rotating dq-axis greatly simplifies the model, as time varying parameters are simplified to a time independent parameters [54,55]. In the rotating reference frame, the dynamic equations representing the behavior of a PMSG are expressed in Equations (4) and (5) [56]:…”
Section: Permanent Magnet Synchronous Generatormentioning
confidence: 99%
“…Nowadays, most countries are promoting the massive integration of renewable energy sources (RES) to replace conventional power plants based on nuclear and fossil fuels [1,2]. Among the different reasons for this transition, the most important include the environmental worry (climate change due to greenhouse gas emissions) and also to reduce the energy dependence on fuels imported from third countries [3,4]. However, RES have a stochastic and uncertain behavior due to their dependence on weather conditions [5].…”
Section: Introductionmentioning
confidence: 99%
“…In the last two decades, electric power systems have experienced very significant changes in their operational requirements, mainly due to a growing share of non-conventional renewable energy in the electricity generation mix, along with the operation of grids with a higher degree of complexity [1][2][3]. From the beginning of the massive electrical generation industry at the beginning of the 20th century, conventional synchronous generators have been responsible for guaranteeing frequency stability [4], among other tasks within the operation of a power system.…”
Section: Introductionmentioning
confidence: 99%
“…From the point of view of the power system, this is seen as a lack of inertial response. To address this issue, previous works have outlined the design and implementation of additional control schemes that provide certain complementary regulation capabilities to certain renewable generators (e.g., photovoltaic [9,10], wind [11,12], hybrid of both [3,13]) and battery energy storage systems [14,15], with the aim of modifying the active power injected into the network in response to variations in frequency, similar to how conventional synchronous generators do; hence, the use of the term "virtual inertia". Further, very interesting review papers addressing inertia and frequency control strategies can be found in [8,16,17].…”
Section: Introductionmentioning
confidence: 99%